Protection against Exotoxin A (ETA) and Pseudomonas aeruginosa Infection in Mice with ETA-Specific Antipeptide Antibodies - El-Zaim, Haissam S. (American Society for Microbiology, 1998)
Pseudomonas aeruginosa is an opportunistic pathogen that causes serious and sometimes fatal infections in the compromised host, especially in patients with major trauma or thermal injuries. Exotoxin A (ETA) is the major and most lethal virulence factor produced by this ubiquitous microorganism. In a recent study (H. S. Elzaim, A. K. Chopra, J. W. Peterson, R. Goodheart, and J. P. Heggers, Infect. Immun. 66:2170–2179, 1998), we identified two major epitopes, one within the translocation domain (amino acid [aa] residues 289 to 333) of ETA and another within the enzymatic domain (aa 610 to 638), by using a panel of antipeptide antibodies. Synthetic peptides representing these two epitopes induced ETA-specific antibodies which were able to abrogate the cytotoxic activity of ETA, as measured by incorporation of [(3)H]leucine into 3T3 fibroblasts. In the present study, these antibodies were tested for the ability to provide protection against ETA and infection with a toxin-producing strain of P. aeruginosa in a mouse model. Antibodies to either of the synthetic peptides conferred protection against ETA. Also, when used for immunization, both peptides induced active immunity to ETA in mice. Antibodies to the peptide representing a region within the enzymatic domain of ETA, in combination with the antibiotic amikacin, enhanced the survival of mice infected with a toxin-producing strain of P. aeruginosa. Thus, antipeptide antibodies specific for ETA might be paired with antibiotic treatment for passive immunization of patients suffering from P. aeruginosa infection.